Análise da competitividade de empreendimentos associativos e cooperativos de coletores de material reciclável - Michalski Filho, Cesario (2011)
The aim of this paper is to identify and report functional areas and the environment in which they live and cooperatives of collectors of recyclable materials which are the factors that hinder their stay in a competitive market. The organization in question are trade as an alternative to income generation and employment for some workers. For the field research was used qualitative methodology, where questionnaires were used for open interviews and direct observation in four projects, three in Curitiba-PR and the metropolitan area and another in the city of Itararé-SP, a municipality situated on the border with the state Paraná and 311 km from state capital of São Paulo. After the analysis of the data found that the organizations studied are located in a very competitive environment, where the main buyers of their products are large companies that have great bargaining power and lower costs when seeking to increase their margins profits. Internally the new developments have deficiencies in its four areas of operations, finance, human resources, marketing and production system, thus impeding their stay in a competitive market.